Role of natural capital in an experience of rural development: the case of Zambrana Abajo, Colinas Bajas Model Forest, Dominican Republic - Gómez Luciano, Cristino A. (2011)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2011